Um ativismo (quase) esquecido: o movimento sufragista e seu impacto na política externa britânica (1914-1918) - Taboada, Carmen Roberta de Oliveira (Universidade do Vale do Rio dos Sinos, 2021)
Gender relations are a recent research topic within the area of International Relations (IR). Therefore, considering the lack of studies and visibility on the subject within this discipline and the international and national political context of several countries, it is extremely necessary that the history and the present are discussed from a perspective that prioritizes gender issues in order so that women conquer their space in the public and private spheres of society. In this sense, this monograph seeks to analyze the possible impact of the British suffrage movement, which campaigned for the female vote, on the United Kingdom's foreign policy during the period of World War I (1914-1918). To this end, the research will be guided by the Feminist Theory of International Relations, especially from the vision of the author Ann Tickner, and by the Foreign Policy Analysis of the Two Level Game, formulated by Robert Putnam. Thus, it is possible to emphasize that, although there are achievements in the struggle for women's civil rights and for the public and political space of women, it is still necessary that they are recognized as actors in the system in order to be able to impact it and change it. The objective of this work is to contribute to a more plural thought in the Academy and to inspire greater female participation in national and international decision-making spaces.
Keywords: Teoria Feminista de Relações Internacionais; Gênero; Política Externa; Jogo de Dois Níveis; Movimento Sufragista; Reino Unido; I Guerra Mundial; Feminist Theory of International Relations; Gender; Foreign Policy; Two Level Game; Suffrage Movement; United Kingdom; World War I